2011
DOI: 10.1002/pen.22144
|View full text |Cite
|
Sign up to set email alerts
|

Melt fracture of two broad molecular weight distribution high‐density polyethylenes

Abstract: The melt fracture instabilities of two broad molecular weight distribution (MWD) high‐density polyethylenes (one Ziegler–Natta and one metallocene HDPEs) are studied as functions of the temperature and geometrical details and type of die (cylindrical, slit, and annular). It is found that sharkskin and other melt fracture phenomena are distinctly different for these resins, despite their almost identical rheology. It is also found that the critical conditions for the onset of various melt fracture phenomena dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Only a small region in the curve exists where rheological instability would occur due to a stress bifurcation. The overall shape of this stress response curve, including the slight bifurcation, is reported in a number of experiments [2,38,39]. At low shear rates the chain ends are fairly evenly distributed throughout the box.…”
mentioning
confidence: 64%
“…Only a small region in the curve exists where rheological instability would occur due to a stress bifurcation. The overall shape of this stress response curve, including the slight bifurcation, is reported in a number of experiments [2,38,39]. At low shear rates the chain ends are fairly evenly distributed throughout the box.…”
mentioning
confidence: 64%
“…Table 1 summarizes some of their molecular characteristics. The m-HDPE was expected to exhibit a better processability since it has a broader molecular weight distribution (MWD), however this was found not to be the case (Ansari et al 2011). Differences in crystallization behavior were proposed as the reason for this observation.…”
Section: Methodsmentioning
confidence: 95%
“…The influence of die geometry in capillary rheometry has been experimentally and numerically discussed in the literature. [ 13–20 ] Experimental studies [ 15,16 ] have shown that the onset and the type of flow instabilities are significantly affected by the die geometry even at a similar range of shear rates. For this reason, both slit (rectangular cross‐section area) and round capillary (circular cross‐section area) dies are used in this investigation.…”
Section: Introductionmentioning
confidence: 99%